Dampak Pengabaian Hak dan Kewajiban Suami Istri terhadap Kekerasan Dalam Rumah Tangga - Wilda Widiatul Hikmah; Kholil Nawawi; Syarifah Gustiawati (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Humans are creatures who have desires or desires within themselves. Marriage is one of the desires and obligations of a human being which is a command from Allah SWT. Marriage has a goal, namely to build a sakinah mawaddah warrahmah family, to make it happen, knowledge and commitment of husband and wife are needed in carrying out their respective rights and obligations. However, in reality there are still many husbands and wives who ignore their rights and obligations and ultimately lead to domestic violence. The purpose of this study is to find out how the impact of neglecting the rights and obligations of husband and wife on domestic violence and to find out the law of neglecting the rights and obligations of husband and wife according to Islamic law and law. This study uses a qualitative method through a descriptive approach. Data collection techniques were obtained from the results of interviews and document studies. The results of this study indicate that the factors and impacts of neglecting the rights and obligations of husband and wife on domestic violence are as follows: 1) Communication factor, lack of communication between husband and wife, causing difficulties in establishing cooperation between the two. 2) Economic factors, lack of a husband's sense of responsibility in terms of providing a living, so that the wife has to earn her own money and does not depend on her husband. 3) Social factors, there are no social boundaries between husband and wife so that the rights and obligations in the household are not fulfilled. Keywords: Impact of Neglect, Rights and Obligations, Husband and Wife, Domestic Violence.